(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The biological remediation capacity of tannery waste polluted soil by individual Aspergillus aculeatus (MH634499.1) isolated from unpolluted soil, Aspergillus niger (MH780917.1) isolated from tannery waste polluted soil and Co-slurry of both fungi was analyzed. From the polluted soil, microbial and physicochemical parameters were determined before amendments and amended tannery waste polluted soil was monitored for two weeks interval up to 12 weeks; Nutrient agar (NA) was used for total heterotrophic bacteria count (THBC), Sabouraud dextrose agar (SDA) for total heterotrophic fungi counts (THFC), minimal salt agar (MSA) for total tannery waste utilizing bacteria counts (TtWUBC) and total tannery waste utilizing fungi counts (TtWUFC) while pH, Phosphorus, Nitrogen, Organic Carbon, potassium, sodium, Calcium, Magnesium, Cation Exchange Capacity and Soil texture as Physicochemical. Twelve (12) conical flasks each with 1000ml sabouraud dextrose broth and colony of each fungi were incubated in a rotary shaker at 300C for 7days. These were used as slurry for bioremediation. The soil polluted with tannery waste 500g each were amended with fungi slurry containing Spore cells 105 per gram of soil in the designed treatments, T1, T2, T3 and T4. The pollution intensity of the tannery waste polluted soil before amendment include THBC (2.5×106 CFU/g), TtWUBC (1.5×106 CFU/g), THFC (1.5×105 CFU/g) and TtWUFC (8×103 CFU/g) microbiologically while pH 7.5, organic carbon (4.7%), Nitrogen (0.22%), Phosphorus (1.25mg/kg), Calcium (3.75mg/kg), Magnesium (3.55mg/kg), sodium (20mg/kg), potassium (12.1mg/kg), CEC (47.3mg/kg) were physicochemical properties. The mean range of the amended tannery waste polluted soil had pH 7.5-8.8 with organic carbon reduced from